Use of the fluid obtained by puncture of cystic hygroma: an alternative method for fetal karyotyping - Maiara A. Floriani; Luiza E. Dorfman; Dayane B. Koshiyama; Tatiana D. Zen; Jorge Alberto B. Telles; André C. Cunha; Paulo Ricardo G. Zen; Rafael Fabiano M. Rosa
ABSTRACT The aim of our study aim was to report the case of a fetus with Turner syndrome (TS) diagnosed by karyotype from cystic hygroma (CH) fluid, highlighting the applications and importance of this procedure. First-trimester screening revealed an increased nuchal translucency measurement, cervical cystic hygroma and head and trunk subcutaneous edema. The presence of oligohydramnios prevented the performance of amniocentesis. We performed puncture of the CH for fetal karyotyping, which revealed X-chromosome monosomy (45,X), compatible with TS. Therefore, the use of CH fluid as an alternative sample for fetal karyotyping may be considered when conventional invasive procedures can not be performed.